Proceedings of the Eighth International Conference on Information and Communication Technologies and Development 2016
DOI: 10.1145/2909609.2909668
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Access Divides

Abstract: Despite the appearance of uniform availability of mobile services, in many locales granular network analyses reveal the persistence of physical access divides. It stands to reason these divides, similar to those at larger scales, are also reflections of community-level social and economic divides. In this research, we examine community-level physical access divides in the context of a Syrian refugee camp. The investigation combines detailed network and organizational analyses to characterize the divides and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Duarte et al [19] highlight that while geo-spatial services provide information to refugees in Germany, refugees' lack of experience in using such digital services may make them ineffective. Research within refugee camps and settlements has also shown how limited internet connectivity [55] and access to technologies [24,51] within these spaces pose a significant challenge for the use of technologies to support refugees. Such technological obstacles contribute to access divides within different refugee communities.…”
Section: Refugees and Cscwmentioning
confidence: 99%
“…Duarte et al [19] highlight that while geo-spatial services provide information to refugees in Germany, refugees' lack of experience in using such digital services may make them ineffective. Research within refugee camps and settlements has also shown how limited internet connectivity [55] and access to technologies [24,51] within these spaces pose a significant challenge for the use of technologies to support refugees. Such technological obstacles contribute to access divides within different refugee communities.…”
Section: Refugees and Cscwmentioning
confidence: 99%
“…In networking, intermittency can be due to several factors, such as a lack of general networking infrastructure [10,28], an overwhelming of infrastructure due to a high level of data traffic [15,29], and failures of dependent infrastructures like electricity [6]. Across these potential causes, intermittency is often seen as a shortcoming of the system, which often entails building or bolstering additional network infrastructures.…”
Section: Background and Related Workmentioning
confidence: 99%